2021
DOI: 10.1177/2048004020982213
|View full text |Cite
|
Sign up to set email alerts
|

Improved low-risk criteria scores for combination therapy of sildenafil and generic bosentan in patients with congenital heart disease with severe pulmonary hypertension: A prospective open label study

Abstract: Objective We evaluated the efficacy and safety of the bosentan as a sequential add-on therapy with sildenafil in pulmonary arterial hypertension with congenital heart disease (PAH-CHD) patients. Material and method Twenty patients who were receiving sildenafil were given generic bosentan for up to a year. Hemodynamic data was collected from cardiac catheterization at pretreatment and at three months. Comparisons were made between the total scores of the four, low-risk criteria adapted from the 2015 ESC/ERS pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Nearly all other PH registries in Europe and the United States that also include CHD comprise all types of group 1 patients (PAH) but differentiate less precisely between clinical subtypes, treatment characteristics, and outcomes of distinct patient groups (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all other PH registries in Europe and the United States that also include CHD comprise all types of group 1 patients (PAH) but differentiate less precisely between clinical subtypes, treatment characteristics, and outcomes of distinct patient groups (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…The reluctance to using combination therapies in PAH-CHD may originate from the fact that, particularly in Eisenmenger syndrome, evidence-based and consensusdriven treatment algorithms are not available, and there is no robust evidence to support the use of PAH combination therapy (23). However, in recent years, some study data and reports have suggested that adults with CHD may also benefit from targeted combination therapy (7,(24)(25)(26)(27)(28). Accordingly, a more aggressive approach is also reflected in the COMPERA-CHD data, as the percentage of initially monotherapy (41%) versus combination therapy (53%) shifted during the observation period in favor of combination therapy.…”
Section: Targeted Medical Pah Treatmentmentioning
confidence: 99%
“…Studies have shown that drugs, such as angiotensin receptor blockers [ 124 ]; prostaglandins [ 11 ]; and ACE [ 13 , 14 ], endothelin-1 [ 99 ], and PDE-5 inhibitors [ 12 ], have a positive impact on mortality and quality of life in patients with CHD. Likewise, treatments, such as riociguat [ 120 ], macitentan [ 98 ], and a combination of bosentan with sildenafil [ 94 ], have given positive results, but studies in pediatric patients are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the exposure plateau for bosentan is reached at a dose of 2 mg/kg twice daily, making the adequate dose up to 4 mg/kg [ 97 ]. Currently, incremental treatment with bosentan along with sildenafil has been shown to improve pulmonary and systemic vascular resistance in a study with patients ranging from 12 to 53 years with CHD and pulmonary arterial hypertension [ 98 ]. However, macitentan, an analogous-to-bosentan pulmonary vasodilator ERA [ 94 ], improved mortality and morbidity in a placebo-controlled trial of bosentan [ 99 ].…”
Section: Drugs For Chd Treatmentmentioning
confidence: 99%
See 1 more Smart Citation